Effect of Dietary Short-Chain Fatty Acids on the Immune Status and Disease Resistance of European Seabass Juveniles - Filipa Fontinha; Nicole Martins; Filippo Bonin; Rui Magalhães; Rafaela Santos; Helena Peres; Aires Oliva-Teles (Fishes)
(1) Background: This study aimed to evaluate the potential of short-chain fatty acids as functional ingredients to improve the immune status and disease resistance of European seabass (Dicentrarchus labrax) juveniles. (2) Methods: For that purpose, triplicate groups of fish with an initial body weight of 15.2 ± 0.03 g were fed isoproteic (43% crude protein) and isolipidic (18% crude lipids) diets supplemented with sodium acetate (SA), sodium propionate (SP), and sodium butyrate (SB) at two inclusion levels: 0.25% and 0.50%. An unsupplemented diet was used as a control. After 56 days of feeding with the experimental diets, fish were intraperitoneally (i.p.) injected with 100 µL of Vibrio anguillarum (1.2 × 107 Colony Forming Units (CFU)/mL) and mortality was recorded for 3 weeks. At the end of the trial, there were no differences in survival between the treatment groups and the control, but survival was higher in fish fed the diet supplemented with SB 0.50 than SP 0.25 (93.3 vs. 66.7%). Compared to the pre-challenge values, and regardless of diet composition, all hematological parameters (hemoglobin, hematocrit, red blood cells, white blood cells) measured decreased after 4 h of bacterial challenge, except for neutrophils which were increased. Independently of diet composition, lysozyme and nitric oxide decreased at 4 and 24 h post infection. Compared to the control, diets supplemented with SA and SP promoted an up-regulation of both pro- and anti-inflammatory cytokines at 4 h after the challenge, while the diets supplemented with SB promoted an up-regulation of pro- and anti-inflammatory cytokines at 24 h after the challenge. (3) Conclusions: Overall, present results suggest that SA and SP provide a fast response to a bacterial challenge in European sea bass juveniles, while SB provides increased survival.